A Computational Logic Application Framework for Service Discovery and Contracting - Torroni, Paolo; Chesani, Federico; Gavanelli, Marco; Alberti, Marco; Cattafi, Massimiliano; Lamma, Evelina; Mello, Paola; Montali, Marco (International journal of web services research, 2011)
In Semantic Web technologies, searching for a service means identifying components that can potentially satisfy user needs in terms of inputs and outputs (discovery) and devise a fruitful interaction with the customer (contracting). In this paper, the authors present an application framework that encompasses both the discovery and the contracting steps in a unified search process. In particular, the authors accommodate service discovery by ontology-based reasoning and contracting by reasoning about behavioural interfaces, published in a formal language. To this purpose, the authors consider a formal approach grounded on Computational Logic. They define, illustrate, and evaluate a framework, called SCIFF Reasoning Engine (SRE), which can establish if a Semantic Web Service and a requester can fruitfully inter-operate, by computing a possible interaction plan based on the behavioural interfaces of both. The same operational machinery used for contracting can be used for runtime verification.